Authorship and text-making in early China - Zhang, Hanmo (Library of sinology, 2018)
"This book presents the first systematic investigation on the four types of authorship in the early history of Chinese text making. It enlightens readers with a careful analysis of the emergence and development of the concept of authorship, hand in hand with text formation in early China, and offers an innovative methodology for all those who are interested in rereading and reappraising early Chinese texts"--Back cover.